Republika Federalna Niemiec wobec państw Partnerstwa Wschodniego w kontekście niemieckiej polityki wschodniej w XXI wieku. Implikacje dla Polski - Garczewski, Krzysztof (Rocznik Polsko-Niemiecki, 2017)
This article presents the relationships of the Federal Republic of Germany with six countries that joined the Eastern Partnership programme: Ukraine, Belarus, Moldova, Armenia, Azerbaijan and Georgia. It also contains an analysis of the German Federal Government’s approach towards the Eastern Partnership project, which was initiated by Poland with the support of Sweden. The author takes account of the implications for Poland of Germany’s policy in this region.